Association of a locus on rat chromosome 4 with anxiety-related behaviors in two selectively bred rat lines - Thaïs M. Hameister; Geison S. Izídio; Victor H. Valiati; André Ramos (Genetics and Molecular Biology, 2008)
The Floripa H and L rat lines, selected for high and low locomotion in the central aversive area of an open field, a widely used emotionality test, were proposed as a model for studying the genetic basis of anxiety. The present study aimed to verify if the QTL Ofil1, mapped to rat chromosome 4 and previously identified as being related to emotionality in another population of rats, contributes to the behavioral variability observed in the Floripa rat lines. To this purpose, rats of five generations of selective breeding were genotyped for two polymorphic markers, D4RAT59 and D4MGH27, flanking Ofil1. Changes in genotype and allele frequencies throughout generations were evaluated in both H and L lines, in order to assess if the bidirectional selection based on behavioral scores induced divergent changes in the genotype of this genome region. There were significant changes in genotype frequencies for both molecular markers, however, only the genotype variations of the D4RAT59 marker were significantly correlated with the variations in the selected phenotype. This result suggests that the region of the genome near D4RAT59 contains one or more genes contributing to the interindividual variation in central locomotion in the open field test.